(untitled) (Analysis in Theory and Applications, 2025)
In the paper, the authors introduce a new subclass of univalent functions associated with the strip domains by using the generalized Sălăgean operator. The bounds of coefficients and Fekete-Szegö inequality for functions in this class are obtained. The results presented here extend some of the earlier results.